Bank Kalbar's Educational Programs for MSME Revitalization and Community Economic Development - Haryono, Didi; Somantri, Gumilar Rusliwa; Gafur, Hanif Saha; Rofii, Muhammad Syaroni; Hidayati, Ajeng (Nomico, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to Indonesia's economy, contributing approximately 60.5% to the Gross Domestic Product (GDP) and employing about 96.9% of the national workforce. Despite the large number of MSMEs and their potential GDP contribution, there is still room for improvement in exports. The government has taken various measures to support MSME development, including policies that encourage digital business growth and education-based training for MSMEs. In West Kalimantan Province (Kalbar), MSMEs play a vital role in regional economic development. Despite their potential, they face several challenges such as access to capital, financial management, and market access. The regional government and the Bank of West Kalimantan have collaborated to revitalize MSMEs post-COVID-19 through various programs, credit schemes, and educational initiatives or training sessions. This study employs both qualitative and quantitative methods with a case study approach. The research results indicate that MSMEs significantly contribute to West Kalimantan's economic development, despite being impacted by the pandemic. The internal and external revitalization strategies implemented by Bank Kalbar have assisted MSMEs in recovery and adapting to digital-based business models. The study concludes that MSMEs in West Kalimantan have the potential to continue growing and thriving as independent economic entities in a digital-based business environment. The revitalization of MSMEs is a result of collaboration between MSME actors, the government, and banking institutions to achieve regional economic stability and recovery.